2015
DOI: 10.3991/ijim.v9i3.4596
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards the Use of Mobile Learning: A Case Study from the Gulf Region

Abstract: Abstract-In the last few years, the way we learn has been shifted dramatically from traditional classrooms depending on printed papers into E-learning depending on digital pages. Mobile learning (M-learning) is a recent technology that has been developed rapidly to deliver E-learning using personal mobile devices without posing any restrictions on time and location. In this work, we investigate students and faculty members' attitudes towards the use of M-learning in higher educational institutions within two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In the last few years, an increased number of research studies were conducted to examine the utilization of mobile devices in several sectors; one of them is the higher education [2], [3], [1], [4], [6], [5]. M-learning has a great influence on the students as well as researchers for developing a robust educational infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, an increased number of research studies were conducted to examine the utilization of mobile devices in several sectors; one of them is the higher education [2], [3], [1], [4], [6], [5]. M-learning has a great influence on the students as well as researchers for developing a robust educational infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the study by [16] indicated through the use of an independent t-test that female educators' perceptions were more positive than males towards the use of M-learning. In contrast, a study by [11] found that male educators' perceptions were more positive towards M-learning than females, while findings by [13] and [6] didn't reveal any significant difference among the academics' perceptions towards the utilization of Mlearning with regard to their gender.…”
Section: Findings Rq1mentioning
confidence: 47%
“…As a limitation, this study has been conducted in order to compare the students' and academics' perceptions towards the utilization of Mlearning within two countries (Oman and UAE) by examining only two factors (gender and country). Due to the reason that there is a limited number of available articles related to educators' attitudes towards the utilization of M-learning in the higher educational universities around the world in general and specifically within the Arab Gulf countries, and as an extension to the work published by [13], this study has been conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations